Homeostasis and food craving in obesity: a functional MRI study - Stopyra, Marion A.; Friederich, Hans-Christoph; Lavandier, Nora; Mönning, Esther; Bendszus, Martin; Herzog, Wolfgang; Simon, Joe J. (International journal of obesity, 2021)
OBJECTIVES: Food intake in obesity has been found to be reward-based and less contingent on homeostatic needs. Accordingly, previous studies investigating neural processing of food cues observed aberrant processing in reward- and control-related brain regions in obesity. To further investigate the relation between homeostasis and food intake, this study investigated the inﬂuence of glucose metabolism on the neuronal response during the regulation of food craving in participants with obesity. - METHODS: Twenty-ﬁve normal-weight and 25 women with obesity were examined on two occasions after receiving either water or glucose directly into the stomach using a nasogastric tube. Participants were blinded to the type of infusion and were required to refrain from eating for 16 h before each visit. An event-related fMRI paradigm was used to investigate the effect of intestinal glucose load on the neuronal response during the regulation of food craving. - RESULTS: A 2 × 2 mixed-model ANOVA revealed that craving regulation was associated with increased activation in fronto-parietal regions in participants with obesity when compared to healthy controls. However, this effect was observed independently from homeostatic satiety. A regression analysis revealed that the reduction of food craving was related to increased activation in the lingual gyrus in individuals with obesity following the infusion of water. - CONCLUSIONS: In participants with obesity, the neuronal response during the regulation of food craving is associated with increased neural cognitive top-down control and increased visual food processing. Since this observation was independent from satiety status, our results indicate a reduced inﬂuence of homeostasis on neural processing during food craving in obesity. This study was registered on clinicaltrials.org: NCT03075371. International Journal of Obesity (2021) 45:2464-2470; https://doi.org/10.1038/s41366-021-00920-4